(untitled) (Journal of Nobel Medical College, 2020)
Seasonal flu or influenza is an acute respiratory illness caused by Influenza virus A and B. The disease is usually self-limiting, but can occasionally lead to dire complications. To prevent the occurrence of these complications, many preventive, as well as therapeutic remedies, have been implicated. Vaccines have shown to reduce morbidity associated with influenza viral infection. In addition to this, if an infection does occur, it may lead to adversities, especially in patients with extremes of ages, i.e., less than 12 and more than 65. The advent of anti-viral medications has helped in a significant reduction in the symptoms associated with this disease. But, as resistance to these chemicals has emerged, this is now contributing to the widespread endemics and pandemics. With this understanding, newer and better drugs are being introduced in the market. One such medication is Baloxavir, a modified version of the novel anti-viral drugs. We conducted a thorough electronic data search on PubMed and Google Scholar. Articles were filtered using the exclusion criteria of, “co-morbid conditions,” immunodeficiency state,” “Chronic Obstructive Pulmonary Disease,” etc. The extracted articles were within a five-year time frame and were free full text. Further information was extracted using cross-references. Articles were screened for duplication. In this literature review, we describe in detail the advantages of Baloxavir to reduce the morbidity associated with Influenza infection.